(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The theories of relativity by Albert Einstein revolutionize how the earth thinks about space, time, mass, energy and gravity. Before Einstein, Newton laws were used to understand the physics of motion. In 1687, Newton studied that gravity affects everything in the cosmos. The similar force of gravity that pulls an apple down from a tree kept the Earth in motion around the sun. This paper examines about space structure: Einstein’s theory of relativity & universe.